Efficiency of distributed application of nitrogen on onion (Allium cepa L.) cultivated as an annual crop - I. I. Irkov; O. N. Uspenskaya; N. I. Bernaz (Овощи России, 2023)
Relevance. Onions in Russia in 2021: Cultivation area – 56.3 thousand hectares; Productivity – 28.6 t/ha; Production – 1608.6 thousand tons; Import from the volume of consumption – 10.7%. Modern varieties and hybrids and plant protection products make it possible to obtain high yields in the conditions of the Non-chernozem zone. The aim of the research is to optimize the parameters and terms of technological operations for the cultivation of onion in an annual crop on alluvial meadow soils of the Non-Chernozem Zone.Materials and methods. The nutrition system of onion plants was tested through distributed nitrogen application during the growing season: Option 1 – (N160P160K160) presowing – (Ca40N10 + K40N20 + K40N20) during the growing season; Option 2 – (N110P110K110) presowing + (Ca40N20 + K40N40 + K40N40) during the growing season. Experience in the use of the microbiological preparation Bisolbi-Plant (Bacillus pumilis) BIS88 together with the 1% humic preparation "Rostok" at a rate of one liter per hectare each to stimulate active growth.Results. At the end of the growing season in the second variant of the nitrogen experiment, the growing season was extended by 7-10 days. The excess yield under the second option for 2021-22 years of research amounted to more than 20.0 t/ha and is significant. The difference in the options for applying the Bisolbi-Plant preparation in 2.8 t/ha with HCP05 – 8.2 t/ha was not significant. The advantage of the variant with the biological preparation is higher plant density by 71.0 thousand units/ha and the absence of signs of bacteriosis. Thus, the distributed application of nitrogen (N110P110K110) presowing + (Ca40N20 + K40N40 + K40N40) during the growing season with irrigation water was significantly more effective than (N160P160K160) presowing + (Ca40N20 + K40N20 + K40N20) during the growing season. There was a tendency to increase the yield and quality of products with the double application of Bisolbi-Plant (BIS88) at a rate of (1.0 + 1.0) l/ha.